Efektivitas Model Pembelajaran Kooperatif Terhadap Hasil Belajar Fisika Di SMA Negeri 3 Makassar - Nisa, Ainin Zahratun; Ali, Muhammad Sidin; Palloan, Pariabti (Universitas PGRI Semarang, 2023)
This research is experimental to analyze the description and differences in the average results of physics learning in groups taught by the cooperative learning model of the TAI, STAD, and TGT types of class X MIPA students at SMA Negeri 3 Makassar. The population in this study were all students in class X MIPA SMA Negeri 3 Makassar as many as 6 classes, the sample was class X MIPA 1 taught the TAI cooperative learning model, class X MIPA 5 taught the STAD type cooperative learning model, and class X MIPA 6 is taught using the TGT cooperative learning model. The instrument in this study was a physics learning achievement test with multiple choice objective questions of 15 items on work and energy, momentum and impulse, and simple harmonic vibrations. The data analysis technique using One Way Analysis Of Variance. Based on the results of the study, (1) the physics learning outcomes using the TAI type cooperative learning model were in the very high category, the STAD and TGT types were in the high category, (2) there was a significant difference in the mean physics learning outcomes between the groups being taught TAI, STAD, and TGT type cooperative learning models (3) the physics learning outcomes of the group taught the TAI type cooperative learning model were significantly higher than the group taught the STAD type cooperative learning model, (4) the group physics learning outcomes that were those taught the TAI cooperative learning model were significantly higher than the group taught the TGT cooperative learning model, (5) the physics learning outcomes of the group taught the STAD type cooperative learning model was significantly higher than the group taught the cooperative learning model type TGT‎.Keywords: Learning Outcomes, Cooperative learning model types TAI, STAD and TGT.